Modelling Demand for Energy Sources as Alternative Energy in the Province of North Sumatra - Yoga Tri Nugraha; Muhammad Irwanto (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
Energy is needed to support daily human activities. Energy usage for the necessities of life is always increasing every year. So far, the energy used comes from fossils, namely coal and oil. Every year fossil energy reserves are decreasing. To overcome these problems, a potential alternative energy source that can replace fossil energy is needed, namely renewable energy. Potential of renewable energy is one of the alternative sources of energy supply and security in the Province of North Sumatra. To ensure the resilience of renewable energy to run sustainably. It is necessary to analyze the potential of renewable energy in North Sumatra by using the Long-range Energy Alternatives Planning System. The results obtained show that North Sumatra has a great potential of energy sources as alternative energy, namely hydro energy and wind energy. It is forecasted that for the year 2027, hydro energy has a potential growth of 3,7 million megawatt-hours and wind energy has a potential growth of 2,2 million megawatt-hours.